Advances and Challenges of Liposome Assisted Drug Delivery - Sercombe, Lisa; Veerati, Tejaswi; Moheimani, Fatemeh; Wu, Sherry Y.; Sood, Anil K.; Hua, Susan (Frontiers in Pharmacology, 2015)
The application of liposomes to assist drug delivery has already had a major impact on many biomedical areas. They have been shown to be beneficial for stabilizing therapeutic compounds, overcoming obstacles to cellular and tissue uptake, and improving biodistribution of compounds to target sites in vivo. This enables effective delivery of encapsulated compounds to target sites while minimizing systemic toxicity. Liposomes present as an attractive delivery system due to their flexible physicochemical and biophysical properties, which allow easy manipulation to address different delivery considerations. Despite considerable research in the last 50 years and the plethora of positive results in preclinical studies, the clinical translation of liposome assisted drug delivery platforms has progressed incrementally. In this review, we will discuss the advances in liposome assisted drug delivery, biological challenges that still remain, and current clinical and experimental use of liposomes for biomedical applications. The translational obstacles of liposomal technology will also be presented.